Clinical and demographic characteristics of an adult population with neuroendocrine tumors - Martínez Montalvo, Carlos Mauricio (2021)
Introduction: Neuroendocrine tumors represent a group of low-incidence neoplasms derived from neuroendocrine cells distributed throughout the body, especially the respiratory and gastrointestinal systems. Objective: To determine the clinical and sociodemographic characteristics of an adult population with neuroendocrine tumors. Materials and methods: In a descriptive cross-sectional study, 91 medical records with a diagnosis of neuroendocrine tumors confirmed by pathology were evaluated between the years 2013 and 2020. Analysis carried out in Microsoft Excel 2013 and Epi Info 7.2. Results: The mean age was 61 years, with a predominance in men (57%). The main antecedents were smoking (35%), arterial hypertension (22%), and COPD (9%). The main symptoms were abdominal pain (43%), weight loss (31%), and cough (26%). According to the origin, those of the foregut were more frequent (75%), predominantly those of the respiratory tract (39.5%). In 21.9%, the origin was unknown. Taking into account 2019 WHO classification, neuroendocrine carcinomas predominated (56%), of which the most frequent was small cell carcinoma. Among the well-differentiated (44%), low-grade (58%) followed by intermediate grade (24%) and low-grade (17%). Metastases were registered in 37% of the cases with mainly liver involvement (49%), lymph nodes (21%), and central nervous system (9%). Death occurred in 24% of cases. Conclusions: The results of the present study coincide with those reported worldwide, highlighting the predominance of tumors of pulmonary origin, as well as similar clinical symptoms according to the affected organs